Dietary hyperoxaluria is not reduced by treatment with lactic acid bacteria - Siener, Roswitha (BioMed Central, 2013)
BACKGROUND: Secondary hyperoxaluria either based on increased intestinal absorption of oxalate (enteric), or high oxalate intake (dietary), is a major risk factor of calcium oxalate urolithiasis. Oxalate-degrading bacteria might have beneficial effects on urinary oxalate excretion resulting from decreased intestinal oxalate concentration and absorption. METHODS: Twenty healthy subjects were studied initially while consuming a diet normal in oxalate. Study participants were then placed on a controlled oxalate-rich diet for a period of 6 weeks. Starting with week 2 of the oxalate-rich diet, participants received 2.6 g/day of a lactic acid bacteria preparation for 5 weeks. Finally, subjects were examined 4 weeks after treatment while consuming again a normal-oxalate diet. Participants provided weekly 24-hour urine specimens. Analyses of blood samples were performed before and at the end of treatment. RESULTS: Urinary oxalate excretion increased significantly from 0.354 ± 0.097 at baseline to 0.542 ± 0.163 mmol/24 h under the oxalate-rich diet and remained elevated until the end of treatment, as did relative supersaturation of calcium oxalate. Plasma oxalate concentration was significantly higher after 5 weeks of treatment compared to baseline. Four weeks after treatment, urinary oxalate excretion and relative supersaturation of calcium oxalate fell to reach initial values. CONCLUSIONS: Persistent dietary hyperoxaluria and increased plasma oxalate concentration can already be induced in healthy subjects without disorders of oxalate metabolism. The study preparation neither reduced urinary oxalate excretion nor plasma oxalate concentration. The preparation may be altered to select for lactic acid bacteria strains with the highest oxalate-degrading activity.